Willingness to share data: Contextual determinants of consumers' decisions to share private data with companies. Issue 2 (21st November 2021) - Ackermann, Kurt Alexander; Burkhalter, Linda; Mildenberger, Thoralf; Frey, Martin; Bearth, Angela
Abstract: In the age of digitalization, customer and consumer data have become a valuable source of information for companies. However, to obtain these data, companies depend on peoples' willingness to share (WTS) their private data with them. By means of a large‐scale online experiment with more than 20, 000 participants, we investigated the extent to which peoples' WTS private data is affected by contextual factors. We complement and extend previous research by (i) simultaneously addressing several contextual factors that companies can largely control themselves, (ii) comparing their relative impacts on WTS, and (iii) explicitly examining interactions between these contextual factors in addition to their specific univariate effects. Concretely, we investigate contextual factors, such as the type of data requested, the purpose for which the data are used, the industry sector a corresponding company belongs to, the type of compensation offered for the shared data, and the degree to which the data allows for personal identification. Our data suggest that all these factors do affect peoples' WTS significantly, while there are also multiple significant interaction effects between these contextual factors. For instance, we found that a better intuitive match between the core business a company is engaged in and the type of data that is requested, results in higher proportions of people who are willing to share the corresponding data with the corresponding company. Hence, companies may benefit from tuning their requests for consumer or customer data according to the specific context in which they operate.